2020
DOI: 10.1371/journal.pone.0238407
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of serotonin receptor 2B improves aortic valve hemodynamics of Notch1 heterozygous mice in a high-cholesterol diet model

Abstract: Calcific aortic valve disease (CAVD) is a deadly disease that is rising in prevalence due to population aging. While the disease is complex and poorly understood, one well-documented driver of valvulopathy is serotonin agonism. Both serotonin overexpression, as seen with carcinoid tumors and drug-related agonism, such as with Fenfluramine use, are linked with various diseases of the valves. Thus, the objective of this study was to determine if genetic ablation or pharmacological antagonism of the 5-HT2B seroto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…In recent years genetic abnormalities, particularly in reduced Notch1 expression, have been regarded as a possible mechanism for calcification in CAVD (45). Interestingly, genetic ablation of the 5HT receptor 2B improved aortic valve hemodynamics of Notch1 heterozygous mice fed high-cholesterol diet (46). Actually, no effective pharmacologic treatment of CAVD has been found (42,47).…”
Section: The Role Of Serotonin In Valvular Heart Disease Due To Disturbance Of Flowmentioning
confidence: 99%
“…In recent years genetic abnormalities, particularly in reduced Notch1 expression, have been regarded as a possible mechanism for calcification in CAVD (45). Interestingly, genetic ablation of the 5HT receptor 2B improved aortic valve hemodynamics of Notch1 heterozygous mice fed high-cholesterol diet (46). Actually, no effective pharmacologic treatment of CAVD has been found (42,47).…”
Section: The Role Of Serotonin In Valvular Heart Disease Due To Disturbance Of Flowmentioning
confidence: 99%
“…Quantitative image analysis was performed to extract area fractions using a previously described, custom MATLAB script. 61,69 Flow Isolation of CD31+ and CD45+ cells for qPCR and CFs for RNA sequencing was performed via FACS. Hearts were excised, and the atria and greater vessels were removed.…”
Section: Wga and Immunofluorescent Stainingmentioning
confidence: 99%
“…The 5-HT 2B R was shown to be involved in vascular heart diseases, including mitral valve prolapse (MVP) [21] and calcific aortic valve disease (CAVD) [22,23]. Overexpression of the 5-HT 2B R in the mitral valve leaflets was found in humans with MVP.…”
Section: Vhdmentioning
confidence: 99%
“…A study in isolated aortic valve interstitial cells (AVICs) in vitro showed that 5-HT 2B R antagonism could prevent AVIC activation, a process associated with CAVD [22]. Recently, the same research group reported that in a high cholesterol diet mouse model, aortic valve hemodynamic development of CAVD could be attenuated by the ablation of the 5-HT 2B gene, but not 5-HT 2B R antagonism [23].…”
Section: Vhdmentioning
confidence: 99%